2013
DOI: 10.1111/his.12258
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of glycerol‐3‐phosphate dehydrogenase 1‐like expression in head and neck squamous cell carcinoma

Abstract: Our results indicate that the GPD1L expression is a strong predictor for local recurrence and survival in HNSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…In the future, the identification of crucial gene signatures will represent a greater advantage in personalized medicine compared with traditional clinicopathological factors 27 . Based on results from our recent studies, several potential biomarkers, such as cyclin D1, enhancer of zeste homologue 2 and glycerol-3-phosphate dehydrogenase 1-like gene, can assist in guiding adjuvant therapy decisions and stratifying high-risk prognostic populations and might have a more accurate efficiency than clinical the TNM stage 18 , 25 , 28 , 29 . The concept of precision medicine based on translational research and novel pathological features is the most promising breakthrough that will further improve the quality of life and long-term survival of patients with head and neck cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, the identification of crucial gene signatures will represent a greater advantage in personalized medicine compared with traditional clinicopathological factors 27 . Based on results from our recent studies, several potential biomarkers, such as cyclin D1, enhancer of zeste homologue 2 and glycerol-3-phosphate dehydrogenase 1-like gene, can assist in guiding adjuvant therapy decisions and stratifying high-risk prognostic populations and might have a more accurate efficiency than clinical the TNM stage 18 , 25 , 28 , 29 . The concept of precision medicine based on translational research and novel pathological features is the most promising breakthrough that will further improve the quality of life and long-term survival of patients with head and neck cancer.…”
Section: Discussionmentioning
confidence: 99%
“…GPD1L has the glycerol-3-phosphate dehydrogenase enzyme activity and is a regulator of HIF-1α stability [40]. And a recent study showed that the GPD1L expression is a strong predictor for local recurrence and survival in HNSCC [39]. HLF belongs to the PAR (proline and acidic amino acid-rich) subfamily of bZIP transcription factors [43, 44], and plays a role in development and circadian rhythm regulation in the mammalian.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, expression of a large number of metastasis-related genes in the PT has been found to correlate with cancer patient overall survival. However, metastatic foci may be more crucial for predicting the prognosis of patients with LNM, particularly OSCC patients with an ~45% chance of suffering metastasis to the neck lymph nodes (5). OSCC tends to metastasize to the cervical lymph nodes (19).…”
Section: Discussionmentioning
confidence: 99%
“…This is mainly due to the high metastatic rates to cervical lymph nodes (2,3), particularly in oral squamous cell carcinoma (OSCC), which accounts for more than 90% of all oral cancer cases (4). In addition, nearly 45% of OSCC patients present with lymph node metastasis (LNM) (5) and their overall survival decreases to 28% (6).…”
Section: Introductionmentioning
confidence: 99%